2019
DOI: 10.1111/cas.13947
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic characterization of fluzoparib, a novel poly(ADP‐ribose) polymerase inhibitor undergoing clinical trials

Abstract: Poly(ADP‐ribose) polymerase (PARP) enzymes play an important role in repairing DNA damage and maintaining genomic stability. Olaparib, the first‐in‐class PARP inhibitor, has shown remarkable clinical benefits in the treatment of BRCA‐mutated ovarian or breast cancer. However, the undesirable hematological toxicity and pharmacokinetic properties of olaparib limit its clinical application. Here, we report the first preclinical characterization of fluzoparib (code name: SHR‐3162), a novel, potent, and orally avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 26 publications
0
55
0
Order By: Relevance
“…Given Talazoparib has a significantly greater PARP trapping capacity, it is hypothesized that PARP trapping may be the underlying mechanism by which sensitivity to radiation is induced (Laird et al, 2018). Fluzoparib has been identified as a novel PARPi, in the early stages of preliminary clinical trials (Wang et al, 2019). Fluzoparib has shown promising results in Phase I/II lung cancer clinical trials as a radiosensitizer and in combination with SHR-1316, a PD-L1 inhibitor (Luo et al, 2019).…”
Section: Lung Cancermentioning
confidence: 99%
“…Given Talazoparib has a significantly greater PARP trapping capacity, it is hypothesized that PARP trapping may be the underlying mechanism by which sensitivity to radiation is induced (Laird et al, 2018). Fluzoparib has been identified as a novel PARPi, in the early stages of preliminary clinical trials (Wang et al, 2019). Fluzoparib has shown promising results in Phase I/II lung cancer clinical trials as a radiosensitizer and in combination with SHR-1316, a PD-L1 inhibitor (Luo et al, 2019).…”
Section: Lung Cancermentioning
confidence: 99%
“…Previous studies reported a G2/M cell cycle arrest after PARPi [34][35][36]. An enhancement of this effect by combination of PARP1 inhibition with irradiation compared to monotherapy was described [37].…”
Section: Discussionmentioning
confidence: 94%
“…Cells were treated with different concentrations of drugs, alone or in combination, as indicated, inhibition rates were determined using sulforhodamine B assays and 50% growth-inhibition concentration (IC 50 ) was calculated using GraphPad Prism software, as described previously. 18 …”
Section: Methodsmentioning
confidence: 99%